PENGARUH PERAN GANDA PEKERJA WANITA TERHADAP KINERJA KARYAWAN DENGAN PENGEMBANGAN KARIR SEBAGAI VARIABEL MEDIASI - Fitriani Rahasdi Ratnaningrum; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
Human resources are an important factor in realizing the pupose of business organizations. PT. Original Textile II Boyolali faces a decline in employee performance, many factors affecting one of the multiple roles. This study aims to determine the effect of Double Role on Performance, Double Role with Career Development, Career Development on Performance, and Double Role on Performance through Career Development. The sample of this research are 87 married woman in PT. Sari Original Color Textile II Boyolali. The type of this research is explanatory research with quantitative approach. With analytical technique using correlation test, determination test, simple regression test, multiple regression test, significance test, test of sobel, and mediation test using SPSS application version 16. The result of this research shows that H1 double role t value equal to -7,653 and the probability significance value <0,05 means that double role influence the performance, H2 double role t value equal to -8,879 and significance value <0,05 meaning multiple roles have a significant effect on career development, H3 career development t value of 9.378 and probability significance value <0.05 which means career development has a significant effect on performance, H4 the result of mediation test with t value equal to -4.4352 and its p-value 0.0000092 is smaller than the 0.05 significance level which means Double Role effect on Performance through Career development with partial meditation